Mortality, recruitment pattern and growth of the white shrimp Litopenaeus schmitti (Crustacea: Penaeidae) from the Gulf of Venezuela - Díaz íngel; Ferrer, Orlando; ílvarezRodolfo; González, Luis; Méndez, Jesús; Corona, Manuel (Ciencia, 2015)
Ver resumen PDF.